OPG-Fc but Not Zoledronic Acid Discontinuation Reverses Osteonecrosis of the Jaws (ONJ) in Mice - Molon, Rafael Scaf de [UNESP]; Shimamoto, Hiroaki; Bezouglaia, Olga; Pirih, Flavia Q.; Dry, Sarah M.; Kostenuik, Paul; Boyce, Rogely W.; Dwyer, Denise; Aghaloo, Tara L.; Tetradis, Sotirios (Wiley-Blackwell, 2015)
Osteonecrosis of the jaws (ONJ) is a significant complication of antiresorptive medications, such as bisphosphonates and denosumab. Antiresorptive discontinuation to promote healing of ONJ lesions remains highly controversial and understudied. Here, we investigated whether antiresorptive discontinuation alters ONJ features in mice, employing the potent bisphosphonate zoledronic acid (ZA) or the receptor activator of NF-B ligand (RANKL) inhibitor OPG-Fc, utilizing previously published ONJ animal models. Mice were treated with vehicle (veh), ZA, or OPG-Fc for 11 weeks to induce ONJ, and antiresorptives were discontinued for 6 or 10 weeks. Maxillae and mandibles were examined by CT imaging and histologically. ONJ features in ZA and OPG-Fc groups included periosteal bone deposition, empty osteocyte lacunae, osteonecrotic areas, and bone exposure, each of which substantially resolved 10 weeks after discontinuing OPG-Fc but not ZA. Full recovery of tartrate-resistant acid phosphatase-positive (TRAP+) osteoclast numbers occurred after discontinuing OPG-Fc but not ZA. Our data provide the first experimental evidence demonstrating that discontinuation of a RANKL inhibitor, but not a bisphosphonate, reverses features of osteonecrosis in mice. It remains unclear whether antiresorptive discontinuation increases the risk of skeletal-related events in patients with bone metastases or fracture risk in osteoporosis patients, but these preclinical data may nonetheless help to inform discussions on the rationale for a drug holiday in managing the ONJ patient. (c) 2015 American Society for Bone and Mineral Research.
Keywords: OSTEONECROSIS OF THE JAW (ONJ); ANTIRESORPTIVES; BISPHOSPHONATES; ZOLEDRONIC ACID; DENOSUMAB; ALVEOLAR BONE; OSTEOCLASTS